Do Ethical Attributes Matter More than Independence? The Moderating Role of Auditor Integrity in Government Audit Quality - Yusniati Yusniati; Farid Fajrin; Mustakim Muchlis (Indonesian Journal of Taxation and Accounting, 2025)
This study aims to examine the influence of independence, spiritual intelligence, and ethical sensitivity on government audit quality, while further investigating the role of auditor integrity as a moderating variable. Employing a causal quantitative approach, primary data were gathered through a questionnaire survey administered to internal auditors at the Provincial Inspectorate of South Sulawesi. Hypothesis testing was conducted using multiple linear regression and Moderated Regression Analysis (MRA). The findings reveal that spiritual intelligence and ethical sensitivity exert a positive and significant impact on audit quality, whereas auditor independence does not exhibit a significant effect. Furthermore, auditor integrity is empirically proven to moderate the relationships between spiritual intelligence and audit quality, as well as between ethical sensitivity and audit quality; however, it fails to moderate the relationship between auditor independence and audit quality. These findings indicate that public sector audit quality is more profoundly determined by the auditor’s value and ethical dimensions rather than mere structural independence. Theoretically, this research enriches the literature on public sector auditing grounded in stewardship and professional ethics; practically, the results emphasize the necessity of strengthening the integrity and ethical capacity of government internal auditors.